EXTRAMEDULLARY INVOLVEMENT IN ACUTE MYELOID LEUKEMIA. A SINGLE CENTER TEN YEARS EXPERIENCE - Luana Fianchi; Martina Quattrone; Marianna Criscuolo; Silvia Bellesi; Giulia Dragonetti; Alessio Maria Edoardo Maraglino; Matteo Bonanni; Patrizia Chiusolo; Simona Sica; Livio Pagano (Mediterranean Journal of Hematology and Infectious Diseases)
The incidence, risk factors and prognostic significance of extramedullary involvement (EMI) in adult patients with acute myeloid leukemia have not been established yet. This study analyzed the clinical and biological characteristics, the impact on prognosis and the cumulative incidence of EMI in a monocentric retrospective study. All consecutive adult pts with a diagnosis of AML observed in our institution between January 2010 and December 2017 were included into the analysis. Overall 346 AMLs were analyzed. The incidence of EMI was 11% (38 pts). The involved sites were: skin (66%), CNS (23%), pleura (7%), lymph nodes (5%), peritoneum (2%), spleen (2%), pancreas (2%), breasts (2%) and bones (2%). Most pts (91%) had only one site of EMI, while 9% had multiple sites affected at the same time. Twenty-four (55%) patients showed signs of EMI at presentation, while extramedullary relapse occurred in 9 pts (24%); 5 pts had EMI both at presentation and at relapse. EMI had a significantly higher frequency in pts with monocytic and myelo-monocytic leukemia subtypes (p<0,0001), MLL rearrangements (p=0.001), trisomy 8 (p=0,02) and a specific cytofluorimetry pattern (CD117-, p= 0,03; CD56-/CD117-, p= 0,04; CD56+/CD117-, p= 0,04). An analysis regarding treatment, OS and DFS was performed only on the 28 patients who experienced EMI at the onset of their disease; one EMI patient received best supportive care and was consequently excluded from OS analysis. The other 27 patients were treated with: conventional chemotherapy (21 pts), hypomethylating agent (5 pts) and low dose citarabine (1 pts); 8 pts (28.5%) received an allogeneic stem cell transplantation (allo-HSCT). Complete remission (CR) rate after induction therapy was 22% with a median DFS of 7.4 months. Median OS of all 27 EMI pts was 11.6 months (range 2-79); this resulted significantly longer for the 8 EMI pts who undergone allo-HSCT than those (19 pts) who didn’t receive this procedure (16.7 vs 8.2 months respectively, p=0.02). Univariate and multivariate analyses showed that undergoing allo-HSCT and achieving CR were the main positive prognostic factors for survival in our population (p<0,0001). This study confirms poor prognosis for EMI pts. Allo-HSCT, applicable however only in some cases, seems to have a crucial role in the therapeutic approach of these patients, being associated with a better prognosis.